Evolutionary engineering towards the optimization of fruit juice fermentations - Gil, Cátia Vieira (2022)
The industry has been exploiting the development of new fermented fruit-based products, since they have potential in the increase of nutritional value and health promotion. However, the fermentation of fruity substrates is often disturbed by the presence of aromatic substances, which while giving to the juice a more intense and natural aroma, can be highly inhibitory for microbial growth. In this context, in the current study, the fermentative performance of the yeasts Schizosaccharomyces pombe and Torulaspora delbrueckii was evaluated in orange juices containing different concentrations of orange essential oils. The impact of orange essential oils on yeast growth profiles in various culture media was also estimated. After observing inhibitory effects on the lag phases of yeast growth, different adaptive evolution approaches were adopted for the two yeasts. The purpose of these experiments was to obtain spontaneous mutants through natural selection, which would provide a phenotype of higher resistance to orange essential oils, assuming that a higher tolerance would lead to decreased growth lag times and therefore would accelerate the fermentation process of “fresh” orange juice (not from concentrate-nfc), which has higher concentrations of orange essential oils. The T. delbrueckii cell-based experimental evolution yielded a stable strain (E16900dT), which showed higher tolerance to orange essential oils. This strain fermented orange juice, which had higher concentrations of orange oils, faster than wild-type cells when inoculated on the same substrate. On the other hand, experimental evolutions starting with Sch. pombe resulted in strains with unstable phenotypes and, therefore, it was not possible to obtain a stable strain more tolerant to orange essential oils. Furthermore, in T. delbrueckii, differences in gene expression of three genes related to cell wall stability (PIR3), occurrence of oxidative stress (GPX2), and plasma membrane integrity (ERG6) were studied in the presence and absence of orange essential oils in chemically defined culture medium. RT-qPCR results revealed an overexpression of a glutathione enzyme peroxidase (Gpx2p), responsible for the cellular response in the presence of oxidative stress, leading to the conclusion that loss of viability of T. delbrueckii in the presence of orange essential oils may be due to oxidative stress.